2018
DOI: 10.1177/2150135118755977
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Cardiac Surgery and Pain Management: After 40 Years in the Desert, Have We Reached the Promised Land?

Abstract: Pain prevention in the pediatric population is mandatory and an integrative aspect of medical practice. Optimal pain management is the right of all patients and the responsibility of all health professionals. The key to adequate pain management is assessing its presence and severity, identifying those who require intervention, and appreciating treatment efficacy. The population of pediatric patients undergoing cardiac surgery is unique in both clinical severity and hemodynamic response to painful stimuli, thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 87 publications
0
17
0
Order By: Relevance
“…Pain management is a critical aspect of postsurgical care in pediatric populations. 1 In pediatric patients undergoing cardiac surgery, postsurgical pain may be associated with hemodynamic instability, which may result in postsurgical morbidity and mortality; therefore, management of postsurgical pain in pediatric patients is of great importance and should be tailored to the individual's needs. 1 Opioids are commonly prescribed for pain management after pediatric surgery.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pain management is a critical aspect of postsurgical care in pediatric populations. 1 In pediatric patients undergoing cardiac surgery, postsurgical pain may be associated with hemodynamic instability, which may result in postsurgical morbidity and mortality; therefore, management of postsurgical pain in pediatric patients is of great importance and should be tailored to the individual's needs. 1 Opioids are commonly prescribed for pain management after pediatric surgery.…”
Section: Introductionmentioning
confidence: 99%
“…1 In pediatric patients undergoing cardiac surgery, postsurgical pain may be associated with hemodynamic instability, which may result in postsurgical morbidity and mortality; therefore, management of postsurgical pain in pediatric patients is of great importance and should be tailored to the individual's needs. 1 Opioids are commonly prescribed for pain management after pediatric surgery. 2,3 In the United States, an estimated ~2% of patients aged 0-14 years and ~10% of patients aged 15-19 years had ≥1 opioid prescription filled in 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Dexmedetomidine is a highly selective α2adrenoceptor agonist that produces dose-dependent sedation, anxiolysis, and analgesia without respiratory depression, unlike other sedatives and opioids. [5][6][7] Its cardiovascular depressant effects are minimal, because of this it has been increasingly used following congenital heart surgeries, due to its combined sedative-analgesic, and anti-sympathetic effects. [8][9][10] Effective postoperative pain management is very important in congenital heart surgery for the maintenance of early and safe extubation and may decrease complication rates and therefore costs.…”
mentioning
confidence: 99%
“…[8][9][10] Effective postoperative pain management is very important in congenital heart surgery for the maintenance of early and safe extubation and may decrease complication rates and therefore costs. [3][4][5] Recent studies have shown that Dex reduces the length of MV and so cardiovascular intensive care unit (CICU) stay, compared to traditional sedativeanalgesic agents, such as propofol, midazolam, fentanyl, and morphine. 5,6 In this retrospective study, we aimed to investigate the sedative and analgesic effects and hemodynamic effects of intravenous dexmedetomidine administration on postoperative pain management compared to morphine consumption in children who underwent congenital cardiac surgery.…”
mentioning
confidence: 99%